Pengaruh Bentuk dan Jarak Purlin terhadap Stabilitas Lateral Rafter pada Struktur Portal Baja - Taufik Ramlan Wijaya (Jurnal Jaring SainTek, 2026)
This paper presents the results of research on the lateral stability of rafter beams in steel frame structures with and without considering the contribution of purlins. Numerical simulations of six three-dimensional finite element models have been carried out by varying the profile and spacing of purlin. The purlin shapes used are C and Z profiles. The purlin spacing used is 1 m, 1.42 m, and 2 m. It was revealed that rafters that include purlin contributions (braced) have a greater elastic critical moment  (Mcr-elastic) capacity, between 321.37% - 444.68%, compared to those that do not include purlins (unbraced). It was also found that due to its greater weak axis inertia, the Z profile has superior performance (by 1.776% – 2.846%) compared to the C profile. It was revealed that increasing the number of purlins (bracing) resulted in Mcr-elastic  ​​values exceeding the plastic moment (Mp) by 18.082% – 52.638%. Meanwhile, if the purlin is not considered (unbraced) the Mcr-elastic  values are below the plastic moment (Mp). It was also found that purlins could effectively shifts the rafter failure mode from elastic lateral torsional buckling to yield condition.